2022
DOI: 10.3389/fpsyt.2022.869070
|View full text |Cite
|
Sign up to set email alerts
|

Sex/Gender as a Factor That Influences Transcranial Magnetic Stimulation Treatment Outcome: Three Potential Biological Explanations

Abstract: Repetitive transcranial magnetic stimulation (rTMS) is a non-invasive brain stimulation technique which is now being used in psychiatry clinics across the world as a therapeutic tool for a variety of neural-circuit based disorders (e.g., major depression, obsessive compulsive disorder, substance use disorders, post-traumatic stress disorder, headache, pain). The higher volume of use and publication of multiple large-scale clinical trials has provided researchers with a unique opportunity to retrospectively eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 41 publications
(43 reference statements)
0
25
0
Order By: Relevance
“…Sexdependent effect of ELF-MFs on biological process in vitro had been previously reported by Baranowska et al [2018] that the effect of pulsed EMFs (7 Hz, 30 mT) on the release of proinflammatory cytokines from adipose-derived stem cells (ADSCs) of Wistar rats were different between male and female. And, more similar phenomenon in in vivo studies [Vallejo and Hidalgo, 2012;Acikgoz et al, 2022;Hanlon and McCalley, 2022]. But, none of these studies uncovered the mechanisms.…”
Section: Discussionmentioning
confidence: 98%
“…Sexdependent effect of ELF-MFs on biological process in vitro had been previously reported by Baranowska et al [2018] that the effect of pulsed EMFs (7 Hz, 30 mT) on the release of proinflammatory cytokines from adipose-derived stem cells (ADSCs) of Wistar rats were different between male and female. And, more similar phenomenon in in vivo studies [Vallejo and Hidalgo, 2012;Acikgoz et al, 2022;Hanlon and McCalley, 2022]. But, none of these studies uncovered the mechanisms.…”
Section: Discussionmentioning
confidence: 98%
“…Analysis of over 5,000 patients treated with TMS for depression found female participants more likely to respond to treatment and enter remission (Sackeim et al, 2020). Several possible biological explanations stemming from differences in patient sex have since been described (Hanlon & McCalley, 2022). We reported unbalanced gender distribution among the two groups, with the 10 Hz group having more women overall and as a higher proportion of participants.…”
Section: Discussionmentioning
confidence: 99%
“…Several possible biological explanations stemming from differences in patient sex have since been described (Hanlon & McCalley, 2022). We reported unbalanced gender distribution among the two groups, with the 10 Hz group having more women overall and as a higher proportion of participants.…”
Section: Discussionmentioning
confidence: 99%
“…Brihmat et al (2022) concluded that young patients usually had greater potential for inducing plasticity changes in response to rTMS than elder participants. Hanlon and McCalley (2022) found that gender maybe a critical influencing factor on the effect of rTMS, and they inferred that the reason may be related with gender difference in gray matter density and gyrification, proximity of the brain to the scalp and cortical excitability. Furthermore, Fitzgerald et al (2016) reported that the response to rTMS was greater in patients with shorter duration of illness.…”
Section: Different Sessionsmentioning
confidence: 99%